Cosmic-ray electron-positron spectrum from 7 GeV to 2 TeV with the Fermi Large Area Telescope - Abdollahi, S.; Ackermann, Markus; Ajello, M.; Atwood, W. B.; Baldini, Luca; Barbiellini, G.; Bastieri, D.; Bellazzini, R.; Bloom, E. D.; Bonino, Raffaella; Brandt, T. J.; Bregeon, J.; et al. (Physical Review D, 2017)
We present a measurement of the cosmic-ray electron + positron spectrum between 7 GeV and 2 TeV performed with almost seven years of data collected with the Fermi Large Area Telescope. We find that the spectrum is well fit by a broken power law with a break energy at about 50 GeV. Above 50 GeV, the spectrum is well described by a single power law with a spectral index of 3.07 +/- 0.02 (stat +/- syst) +/- 0.04 (energy measurement). An exponential cutoff lower than 1.8 TeV is excluded at 95% CL.
CRIS-Team WoS Importer:2020-01-15